2010
DOI: 10.1598/jaal.54.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Secondary English Learners to Understand, Analyze, and Write Interpretive Essays About Theme

Abstract: Members of a site of the California Writing Project conducted the study in this article in partnership with a large, urban, low‐SES school district where 93% of the students speak English as a second language and 69% are designated Limited English Proficient. Over an eight‐year period, a relatively stable group of 55 secondary teachers engaged in ongoing professional development implemented a cognitive strategies approach to reading and writing instruction, making visible for approximately 2,000 students per y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
(4 reference statements)
0
13
0
1
Order By: Relevance
“…Such an uncertain knowledge base, among ELA and ESL teachers alike, points to a widespread lack of pedagogical writing expertise specific to ELLs. These findings suggest that professional development specifically related to writing instruction and assessment for ELLs, such as that experienced by teachers in the longitudinal study conducted by Olson and her colleagues (Olson & Land, 2007;Olson et al, 2011Olson et al, , 2012, might help empower these teachers to differentiate for the ELL writers in their classrooms.…”
Section: Teachers' Perceptions Of Ecological Tensionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Such an uncertain knowledge base, among ELA and ESL teachers alike, points to a widespread lack of pedagogical writing expertise specific to ELLs. These findings suggest that professional development specifically related to writing instruction and assessment for ELLs, such as that experienced by teachers in the longitudinal study conducted by Olson and her colleagues (Olson & Land, 2007;Olson et al, 2011Olson et al, , 2012, might help empower these teachers to differentiate for the ELL writers in their classrooms.…”
Section: Teachers' Perceptions Of Ecological Tensionsmentioning
confidence: 90%
“…Lee () found that focused coursework on teaching secondary EFL writing, specifically on using formative assessments as part of the writing process, helped a case‐study teacher negotiate differences between school policies and knowledge gained through coursework. In the U.S. context, Olson and colleagues (Olson, Kim, & Scarcella, ; Olson & Land, ; Olson, Land, Anselmi, & AuBuchon, ) found a significant positive difference in the analytic writing scores of those secondary ELLs in the United States whose teachers were trained to use a cognitive strategies approach to teaching interpretive reading and analytical writing. Zwiers's () action research, an individualized professional development project, provided the opportunity for an ESL teacher to better understand instruction for ELLs in Grades 7–9, including writing instruction and assessment.…”
Section: Research On Professional Pedagogical and Institutional Issmentioning
confidence: 99%
“…Nina and Jacob's group had identified "identity crisis" and "quest for discovery" from the teachergenerated list and combined elements of these to form the theme "quest for inner knowledge." Whereas students can be challenged in distinguishing theme from topic, character, and plot (Olson, Land, Anselmi, & AuBuchon, 2010), in this case, the use of teacher-generated examples, scaffolding of textual evidence, and group collaboration supported identification of themes. Aspects of curation (Potter, 2011) were evident as students located written language that resonated with their experience of the novel in the teacherdeveloped list of sample novel themes.…”
Section: Ninamentioning
confidence: 95%
“…Con el fin de erradicar las deficiencias en comprensión y producción de textos que presentan los niños de segundo grado de básica primaria, los maestros en general se esfuerzan por aplicar diversas estrategias metodológicas (Olson et al, 2010;Regan & Berkeley, 2012;Villalón et al, 2011), no todas ellas con resultados efectivos (Corcoran & Silander, 2009). Para efectos de esta investigación, la estrategia didáctica involucró el uso de las Tecnologías de la Información y la Comunicación, más específicamente el uso del procesador de textos como instrumento complementario al cuaderno de escritura a mano alzada.…”
Section: Métodounclassified